PENGARUH KOMPOSISI MEDIA TANAM DAN UKURAN POLYBAG TERHADAP PERTUMBUHAN DAN HASIL PANEN SELADA MERAH (Lactuca sativa L.) - Lestari, Anti; Widyawati, Nugraheni (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2023)
[THE EFFECT OF PLANTING MEDIA COMPOSITION AND POLYBAG SIZE ON THE GROWTH AND YIELD OF RED LETTUCE (Lactuca sativa L.) ]. The composition of the growing media and the size of the polybag play an important role in container vegetable production, as they are related to the availability of nutrients, water, and root space in the growing media for the plant to grow. The objective of the study was to determine the effect of planting media composition and polybag size on the growth and yield of red lettuce (Lactuca sativa L). A factorial experiment with two treatment factors was conducted using a randomized block design (RCBD) with three replications. The first factor was the growing medium, which consisted of soil, rice husk charcoal, and goat manure in the composition of 1:2:3, 2:3:1, and 3:1:2. The second factor was the polybag size, which consisted of 15 cm x 15 cm, 20 cm x 20 cm, and 20 cm x 25 cm. The results showed that the growing media composed of soil, husk charcoal, goat manure with a composition of 1:2:3 had a higher N nutrient content and produced higher growth of red lettuce plants compared to other compositions, as shown by plant height, stem diameter, number of leaves, leaf area, shoot fresh weight, and root fresh weight. Plant growth also increased as the size of the polybag used increases.